Contentment according to Imam Al-Razi in his book Gardens of Truths - Lamia Abdel Hassan Al-Nasseri,; Mohamed Hadi Shehab, (Islamic Sciences Journal, 2024)
ABSTRACT Contentment is one of the greatest characteristics of a person, as it means contentment with the blessings that Allah Almighty divides for him, whether they are few or many, and whoever achieves contentment will obtain the satisfaction of Allah , Blessed and Most High, which is what he seeks and hopes for. Due to the importance and status of this characteristic, it has been frequently mentioned and encouraged in the Holy Qur’an. And the purifying Sunnah of the Prophet. The Messenger of God (may God’s prayers and peace be upon him) would often remind and warn his companions (may Allah be pleased with them) about contentment, abandoning the world, and not paying attention to sustenance from it, and that success is associated with contentment after Islam. And since he, may God’s prayers and peace be upon him, had the highest example in contentment and in other things, it was best exemplified by it. Then, the honorable companions and those who came after them who followed them were characterized and possessed conviction, following the example of their Messenger, may Allah’s prayers and peace be upon him, and in compliance with his guidance. They encouraged it and recommended it to those who came after them. Their students and others adhere to it, because with it wealth is achieved and life is good, and the soul rises above the trappings and adornments of the world, and if it exists, it does not become attached to it.